Pelatihan Digitalisasi Pemasaran Produk KWT Sejahtera Kelurahan Curup Jare - Siti Muntari; Elpita Aisah; Apriana Apriana (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
The aim of this service is to provide assistance with marketing promotions for the products of Sejatra Farmer Groups in the Curu Jare sub-district. Problems (1) Limited knowledge about technological advances also makes it difficult for the Curup Jare Women's Farmers Group (KWT) to expand the market, (2) lack of knowledge about the importance of business digitalization in the current modern era, (3) there is no online social media available. take advantage of (3) planning and implementation in the use of technology which is still limited to just updating personal status and modest business activities. A solution that can be used as an alternative is assistance with marketing methods through social media. This assistance utilizes social media such as Facebook, Instagram and YouTube to manage them. The result of this assistance is that the women's farming group can utilize technology in promoting the products they sell so that they can increase sales results. This means getting education regarding the theory of digital product marketing through effective and targeted social media. The output targets of this PkM activity are: 1) increased knowledge and skills of partners, 2) scientific publications in national journals with published status.